Pooled CRISPR Screens in Drosophila Cells. Issue 1 (6th November 2019) - Viswanatha, Raghuvir; Brathwaite, Roderick; Hu, Yanhui; Li, Zhongchi; Rodiger, Jonathan; Merckaert, Pierre; Chung, Verena; Mohr, Stephanie E.; Perrimon, Norbert
Abstract: High‐throughput screens in Drosophila melanogaster cell lines have led to discovery of conserved gene functions related to signal transduction, host‐pathogen interactions, ion transport, and more. CRISPR/Cas9 technology has opened the door to new types of large‐scale cell‐based screens. Whereas array‐format screens require liquid handling automation and assay miniaturization, pooled‐format screens, in which reagents are introduced at random and in bulk, can be done in a standard lab setting. We provide a detailed protocol for conducting and evaluating genome‐wide CRISPR single guide RNA (sgRNA) pooled screens in Drosophila S2R+ cultured cells. Specifically, we provide step‐by‐step instructions for library design and production, optimization of cytotoxin‐based selection assays, genome‐scale screening, and data analysis. This type of project takes ∼3 months to complete. Results can be used in follow‐up studies performed in vivo in Drosophila, mammalian cells, and/or other systems. © 2019 by John Wiley & Sons, Inc. Basic Protocol : Pooled‐format screening with Cas9‐expressing Drosophila S2R+ cells in the presence of cytotoxin Support Protocol 1 : Optimization of cytotoxin concentration for Drosophila cell screening Support Protocol 2 : CRISPR sgRNA library design and production for Drosophila cell screening Support Protocol 3 : Barcode deconvolution and analysis of screening data